No mundo de hoje: atitudes perante as pessoas idosas - Palmeirão, Cristina (2012)
This study focused on the analysis of surveys applied to school-age children, to identify their attitudes associated with the elderly. Simultaneously, we wanted to assess whether gender factors, socio-economic conditions and contexts influence the construction of attitudes towards the elderly. The Kogan Scale was the tool used to observe the attitudes of children to the elderly. The use of this scale required the translation of the original version into Portuguese and suitability for specific purposes. The final version includes only 10 of the 17 pairs of questions (34 items), a total of 20 items. In terms of sample, the study now presented was composed of 463 school-age children from the districts of Porto and Braga attending public and private schools. Research results suggest positive attitudes to the elderly in particular in ‘cohabitation’, ‘heterogeneity’, ‘history’ and ‘humor’ and less positive on the dimensions of ‘health’ and ‘relationship with the young’. One way that needs to be improved for the benefi t of a society that is intended to be supportive and for all ages.